Life is a value – the situation of and opportunities for people with Down syndrome - Steinbach, Éva; Hegedűs, Ákos (European Integration Studies, 2024)
We consider life as a fundamental value and treat it as an axiom. Nevertheless, this critically important right is frequently attacked. The most dangerous of these attacks occur when we pass judgement on difficult issues without sufficient caution. This can determine when and where life can have opportunities, especially when it is fragile and small. The Fundamental Law of Hungary begins its enumeration of fundamental rights with the statement that ‘human dignity shall be inviolable’. It then goes on to say that ‘every human being shall have the right to life and human dignity; the life of the foetus shall be protected from the moment of conception’. It is clear from this wording that the law recognises the beginning of life at live birth but also protects the foetus from conception as part of the process leading to life. Unfortunately, this protection is not without discrimination. Families encountering Down syndrome face numerous challenges from the moment of diagnosis. It is apparent from judicial practice that some form of assistance is sought to be provided to families in difficult situations. The question is how effective this assistance is and how it affects the families and the attitude of health care providers. The aim of this study is to raise the issues that counteract life as a value, taking into account the perspectives of the very lovable individuals with Down syndrome.